Comparative Study between Bronchial Blocker and Left Double Lumen Endotracheal Tube for One Lung Ventilation in Right Video-Assisted Thoracoscopic Surgery (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background: Double lumen endotracheal tubes (DLT) and bronchial Blockers (BB) have both beenused for lung isolation in video-assisted thoracic surgery (VATS) with some inherent demerits.Thoughnot well studied is widely thought that DLT provides faster and better quality of lung collapse.Objective: The aim of this study was to compare the quality of lung deflation of a left sided double lumenendotracheal tube with a broncheal blocker for one lung ventilation in video-assisted thoracic surgery.Materials methods: A total forty adult patients have been assigned to either DLT or BB group whoundergoing VATS procedure for mediastenal mass surgery. Correct placement of airway was confirmed byfiber optic bronchoscopy. The variables assessed were: 1. Time required for correct placement of device, 2.Time taken for lung collapse, 3. Quality of Lung collapse, 4. Number of times of airway mal-positioned, 5.Changes of blood pressure and heart rate at baseline (T1) and immediate before (T2) and after (T3) intubationand one minute after (T4) intubation, 6. Number of patients with hypoxemia (Spo2